Ensino de programação orientada a objetos na educação profissional por meio do desenvolvimento de jogos apoiado pelo ambiente greenfoot - Richter, Cleitom José (2019)
This dissertation is associated with the research line Development in Network Educational Technologies of the Graduate Program in Educational Network Technologies of the Universidade Federal de Santa Maria (UFSM) and describes an action research on the teaching of Object Oriented Programming (OOP), from a game development perspective. The motivation for this proposal stems from the fact that, unlike what can be imagined, the use of technologies does not make today's young people "experts" in computing, since, according to studies by Souza, Batista and Barbosa (2016), teaching and learning programming are considered by many teachers and students a difficult process. For this reason, the disciplines that deal with the teaching of computer programming in computer courses suffer from the difficulties of the students. These problems are also verified in the IFFAR Campus Santo Augusto Technical Computer Science Course, since students present great difficulties in understanding programming concepts, especially those involving OOP. In this sense, the present research sought to understand how the development of games can contribute and facilitate the appropriation of the OOP concepts. Such research came from the creation of game prototypes with support of the Greenfoot development environment. The proposed theme for this study arises from the intention to use the motivation found in games to overcome the difficulties of teaching and learning object oriented programming. It is an applied research with a qualitative-quantitative approach that aims to generate knowledge that will result in reflections on professional practice and to improve programming teaching. For this research, two classes were selected from the IFFAR Campus Santo Augusto course in Computer Science, Integrated in High School (3rd year), with each class consisting of 20 to 26 students. The actions of this proposal were developed in the discipline of Programming Language III and, in both classes, the mentioned discipline was given by the same research professor. The development of the proposal was guided by the structuring of Study Units, addressing the development of game prototypes with the intrinsic purpose of providing conditions for learning object orientation concepts, as well as promoting improvement in didactic interventions in the teaching of computer programming. From the research, it was possible to perceive good acceptance of the students to the proposal, according to the opinions collected in a questionnaire answered by the participants of the research. It was also possible to verify that there was evolution in student learning, as evidenced by statistical tests performed with comparative results of the evaluation performed through the development of conceptual maps before and after interventions. An orientation guide was also produced to be used by professionals in the area to teach OOP.